Molecular mechanisms underlying caveolin-1 mediated membrane curvature - Prakash, Shikha; Malshikare, Hrushikesh; Sengupta, Durba (Journal of Membrane Biology, 2022)
Caveolin-1 is one of the main protein components of caveolae that acts as a mechanosensor at the cell membrane. The interactions of caveolin-1 with membranes have been shown to lead to complex effects such as curvature and the clustering of specific lipids. Here, we review the emerging concepts on the molecular interactions of caveolin-1, with a focus on insights from coarse-grain molecular dynamics simulations. Consensus structural models of caveolin-1 report a helix-turn-helix core motif with flanking domains of higher disorder that could be membrane composition dependent. Caveolin-1 appears to be mainly surface-bound and does not embed very deep in the membrane to which it is bound. The most interesting aspect of caveolin-1 membrane binding is the interplay of cholesterol clustering and membrane curvature. Although cholesterol has been reported to cluster in the vicinity of caveolin-1 by several approaches, simulations show that the clustering is maximal in membrane leaflet opposing the surface-bound caveolin-1. The intrinsic negative curvature of cholesterol appears to stabilize the negative curvature in the opposing leaflet. In fact, the simulations show that blocking cholesterol clustering (through artificial position restraints) blocks membrane curvature, and vice versa. Concomitant with cholesterol clustering is sphingomyelin clustering, again in the opposing leaflet, but in a concentration-dependent manner. The differential stress due to caveolin-1 binding and the inherent asymmetry of the membrane leaflets could be the determinant for membrane curvature and needs to be further probed. The review is an important step to reconcile the molecular level details emerging from simulations with the mesoscopic details provided by state of the art experimental approaches. [GRAPHICS] .
Keywords: Cholesterol clustering; Membrane curvature; Protein-lipid interactions